GovTech Maturity Index : The State of Public Sector Digital Transformation - World Bank (World Bank, Washington, DC, 2021)
The GovTech maturity index (GTMI) presented in this report has been developed as part of the GovTech initiative. The rationale for the GTMI is to introduce a measure of GovTech maturity in four focus areas - core government systems, service delivery, citizen engagement, and GovTech enablers. This index is the most comprehensive measure of digital transformation in the public sector and has been constructed for 198 economies using consistent data sources. The key findings are delineated in several categories to highlight: the important characteristics of the GovTech focal areas; the existence or lack thereof of an enabling environment to foster the implementation of GovTech solutions; the relationship between the GTMI and existing GovTech indices; and best practices from around the world.